Update on the Functional Assessment of Currently Employed Technology Scale (FACETS) 4.0 - Charles M. Lepkowsky (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
In the absence of data indicating that older adults use information technology (IT) to communicate with health care providers or insurers, Medicare, private insurers, and health care providers have increasingly relied on websites and IT to communicate with patients. The FACETS (Functional Assessment of Currently Employed Technology Scale) evaluates a person’s use of various information technologies (ITs). Research using FACETS has demonstrated that use of the internet and other IT declines significantly with increasing age beyond 60 years, especially for accessing health care. The default usage of IT for obtaining health care is being highlighted as a barrier to care in the context of the current COVID-19 problem. This chapter reviews the current status of FACETS findings in the context of the COVID-19 pandemic. Recommendations are made to improve access to care and to increase the use of FACETS to determine which media are most available to older adults for accessing health care.